2013
DOI: 10.1111/jir.12064
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supportive and interfering control as predictors of adaptive and social development in children with and without developmental delays

Abstract: Background Parents of children with developmental delays (DD) have been found to use more controlling behaviour with their children than parents of children with typical development (TD). While controlling behaviour is related to poorer developmental outcomes in TD children, there is little research on how it predicts outcomes in DD children. Furthermore, existing research tends to use inconsistent or non-specific definitions of controlling behaviour, often combining parent control which follows the child’s go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
(85 reference statements)
2
34
0
Order By: Relevance
“…On the other hand, there is evidence that supportive directive acts (e.g., parental control which follows the child's goal) predict better social skills for children with developmental delay. However, mothers of children with developmental delay typically use more interfering than supportive directives, and more interfering directives predict lower adaptive and social skills for children with developmental delay (Green, Caplan, Baker, 2013). Overall, evidence suggests the use of nondirective play and following the child's lead may help to improve language skills in children with developmental delay (Koegel, Koegel, & Surratt, 1992).…”
Section: Parent-child Interactionsmentioning
confidence: 99%
“…On the other hand, there is evidence that supportive directive acts (e.g., parental control which follows the child's goal) predict better social skills for children with developmental delay. However, mothers of children with developmental delay typically use more interfering than supportive directives, and more interfering directives predict lower adaptive and social skills for children with developmental delay (Green, Caplan, Baker, 2013). Overall, evidence suggests the use of nondirective play and following the child's lead may help to improve language skills in children with developmental delay (Koegel, Koegel, & Surratt, 1992).…”
Section: Parent-child Interactionsmentioning
confidence: 99%
“…It has been posited that infants with developmental challenges may benefit from a more directive interaction style that provides scaffolding to elicit desired behaviors (Marfo, 1992), because their more limited repertoire of social initiation and play may provide parents with fewer opportunities to follow their child’s lead (Saint-Georges et al, 2011; Slonims, Cox, & McConachie, 2006; van IJzendoorn et al, 2007; Zwaigenbaum et al, 2005). However, in contrast to maternal responsiveness, the effect of maternal directiveness on the social engagement of infants and children with developmental challenges is less clear, with some studies finding a positive association (Doussard-Roosevelt et al, 2003; Green et al, 2014) and others finding no association (Wan et al, 2012, 2013) or a negative association (Landry, Smith, Miller-Loncar, & Swank, 1998). It has been suggested that typically developing children may be equipped with resources that allow them to be relatively more resilient to the effects of maternal directiveness on social development than are children with developmental challenges (Green et al, 2014).…”
mentioning
confidence: 97%
“…However, in contrast to maternal responsiveness, the effect of maternal directiveness on the social engagement of infants and children with developmental challenges is less clear, with some studies finding a positive association (Doussard-Roosevelt et al, 2003; Green et al, 2014) and others finding no association (Wan et al, 2012, 2013) or a negative association (Landry, Smith, Miller-Loncar, & Swank, 1998). It has been suggested that typically developing children may be equipped with resources that allow them to be relatively more resilient to the effects of maternal directiveness on social development than are children with developmental challenges (Green et al, 2014). …”
mentioning
confidence: 97%
“…; Green et al . ). Evidence suggests that special education teachers use more directives with students with Down Syndrome compared with teachers of TD students (Engevik et al .…”
Section: Impacts Of Children's Characteristics On Caregivers' Behaviourmentioning
confidence: 97%